2022
DOI: 10.1038/s41598-022-21472-1
|View full text |Cite
|
Sign up to set email alerts
|

DEB-TACE combined with hepatic artery infusion chemotherapy might be an affordable treatment option for advanced stage of HCC

Abstract: Alternative treatment modalities are necessary because of the low response rates and unsuitability of molecular-targeted agents (MTA) and/or immune checkpoint inhibitors (iCIs) in HCC patients. Therefore, we analyzed whether drug-eluting beads (DEB)-transcatheter arterial chemoembolization (TACE) with low-dose-FP (Ultra-FP) therapy could improve the efficacy and safety of treatment in difficult-to-treat HCC patients, especially those with advanced stage HCC. From November 2017 to April 2021, 118 consecutive pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…The findings revealed that patients treated with TACE plus HAIC demonstrated improved survival outcomes, enhanced tumor response rates, and comparable risks of adverse events compared to those receiving TACE alone. Notably, previous single-arm studies have also reported on the efficacy of TACE plus HAIC, 16 - 18 suggesting that this combined treatment modality may emerge as another viable option for individuals with unresectable HCC. A combination strategy such as this offers numerous advantages: TACE disrupts tumor blood flow, leading to prolonged exposure of the tumor to high concentrations of chemotherapy drugs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings revealed that patients treated with TACE plus HAIC demonstrated improved survival outcomes, enhanced tumor response rates, and comparable risks of adverse events compared to those receiving TACE alone. Notably, previous single-arm studies have also reported on the efficacy of TACE plus HAIC, 16 - 18 suggesting that this combined treatment modality may emerge as another viable option for individuals with unresectable HCC. A combination strategy such as this offers numerous advantages: TACE disrupts tumor blood flow, leading to prolonged exposure of the tumor to high concentrations of chemotherapy drugs.…”
Section: Discussionmentioning
confidence: 99%
“… 14 , 15 Recent studies, particularly in East Asia, have investigated the efficacy and safety of combining TACE and HAIC for unresectable HCC. 16 - 18 Comparative to TACE monotherapy, the synergistic effects of TACE plus HAIC not only induce partial tumor necrosis and diminish tumor volume by impeding blood supply but also enhance antitumor immune responses triggered by the resulting necrotic tissue. Overall, the independent antitumor mechanisms of chemoembolization, combined with the localized high drug concentration achieved through HAIC, may collectively achieve superior therapeutic effects and reduce the risk of chemotherapy resistance-associated tumor progression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemotherapy remains the primary treatment modality for advanced-stage HCC diagnoses. 7,8 Therefore, the development of novel chemotherapy strategies for HCC is an urgent necessity across all stages of HCC treatment.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the scarcity of available organs for transplantation, the high risk of relapse, and late-stage detection, these treatment choices are limited to a small subset of patients. Chemotherapy remains the primary treatment modality for advanced-stage HCC diagnoses. , Therefore, the development of novel chemotherapy strategies for HCC is an urgent necessity across all stages of HCC treatment.…”
Section: Introductionmentioning
confidence: 99%